Employment status, employment conditions, and limiting illness: prospective evidence from the British household panel survey 1991–2001. Issue 6 (13th May 2004) - Bartley, M; Sacker, A; Clarke, P
Abstract : Objectives: To assess the relation of the incidence of, and recovery from, limiting illness to employment status, occupational social class, and income over time in an initially healthy sample of working age men and women. Methods: Cox proportional hazards models. Results: There were large differences in the risk of limiting illness according to occupational social class, with men and women in the least favourable employment conditions nearly four times more likely to become ill than those in the most favourable. Unemployment and economic inactivity also had a powerful effect on illness incidence. Limiting illness was not a permanent state for most participants in the study. Employment status was also related to recovery. Conclusions: Having secure employment in favourable working conditions greatly reduces the risk of healthy people developing limiting illness. Secure employment increases the likelihood of recovery. These findings have considerable implications for both health inequality and economic policies.